Peran Badan Permusyawaratan Kampong (BPK) dalam Pembentukan Peraturan Kampong Subulussalam, Kecamatan Simpang Kiri, Subulussalam - Tilarso, Diki; Warjio, Warjio; Adam, Adam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The Kampong Consultative Body (BPK) is one of the elements of the village administration that plays the most role in making Kampong regulations, the lack of socialization of regulations made by village officials with the BPK is a problem in the process of drafting and enacting regulations that are not in accordance with what is desired by the community so it is still Many violate village regulations. This study aims to determine and analyze the role of BPK in the formation of village regulations and the obstacles faced by BPK in Kampong Subulussalam, Simpang Kiri District, Subulussalam City. The research used was descriptive method, and the data analysis technique used descriptive qualitative. The results of the research show that BPK Subulussalam in making village regulations has acted as a stabilizer, innovator, modernizer and pioneer, but still does not play a role as its own implementer. BPK has difficulties in carrying out its role It is recommended that BPK members adhere to the principle of prioritizing the public interest above the interests of the group. Each member of the BPK needs to better understand that all parties, including members of the BPK without exception, must comply with the established regulations.